FATIGUE TEST AND FINITE ELEMENT ANALYSIS ON MSD OF STRUCTURE CONTAINING MULTI-ROW HOLES - SUN HanBin; DONG DengKe; CHEN Li; CHANG WenKui (Jixie qiangdu)
Based on the fatigue test of three-row parallel holes without prefabricated cracks,the law of multiple site damage（MSD） for multi-detail structures with similar stress levels was studied. In order to study the interference effect between the cracks in the MSD structure,the FRANC2 D/L was used to calculate and analyze the crack stress intensity factor of four cracking modes:main crack,equal-length double-sided crack,equal-length single-double crack and single-hole isometric crack. The calculation results show that the crack is mainly affected by the interference of the stress concentration of the cracked hole in the initial stage of crack propagation. The dimensionless stress intensity factors of the cracks are similar in the four modes. As the crack length increases,both the test and finite element results show that the interference between the cracks significantly accelerates the crack propagation rate.